An assessment on level of knowledge, attitude and practices (KAP) of hotel management students towards occupational safety and health / Nur Farah Liyana Mohd Akhir - Mohd Akhir, Farah Liyana (2024)
There are many trainings related to safety and health conducted with regards to minimize the numbers of accidents but not focusing on Hotel Management students. This thesis aims on assessment on level of knowledge, attitude, and practices of Hotel Management students towards Occupational Safety and Health (OSH). A structured questionnaire was used and total of 186 Hotel Management students was assessed on knowledge, attitude, and practices. The item from the questionnaire is divided into four section which is emphasizes on the demographic, level of knowledge, attitude, and practices towards OSH. Study found that the level of knowledge of the hotel management students is high, attitude is positive and occupational safety and health practices among Hotel Management students are at good level. The result shown that there is significant correlation between occupational safety and health practice toward occupational safety and health knowledge (r=0.688, p=0.000) and attitude (r=0.660, p=0.000). Result also shows that attitudes become the predictor to practices towards occupational safety and health among hotel management students. The implementation of occupational safety and health at higher institutions should be a combination of programs such as seminar, awareness campaign and safety training. This will ensure the level of awareness about safety becomes more effective and comprehensive.